Are Complications After the Bernese Periacetabular Osteotomy Associated With Subsequent Outcomes Scores?. Issue 5 (May 2019) - Wells, Joel; Schoenecker, Perry; Petrie, Jeff; Thomason, Kayla; Goss, Charles W.; Clohisy, John C.
Abstract: Background: The Bernese periacetabular osteotomy (PAO) continues to be a commonly performed nonarthroplasty option to treat acetabular dysplasia, but only a few short-term studies have evaluated complications rigorously after PAO. Questions/purposes: (1) What complications are observed at 10-year mean followup of the Bernese PAO in patients with symptomatic acetabular dysplasia? (2) What factors are associated with these complications? (3) Do these complications affect clinical outcome scores? Methods: We reviewed 238 hips in 206 patients treated with PAO from July 1994 to August 2008. Only PAOs performed for symptomatic acetabular dysplasia and those that had at a minimum 4-year followup were included. Patients who went on to THA before 4 years were included in the study. Patients with hip pain who presented with a clinical presentation of symptomatic acetabular dysplasia, radiographic evidence of femoral head uncovering, and a lateral center-edge angle < 25° were considered for PAO and no other juxtaacetabular osteotomy was offered other than PAO. Sixty-two hips had diagnoses other than acetabular dysplasia and 22 were lost to followup. The remaining 154 hips (129 patients) were evaluated by chart review at a mean of 10 years (range, 1.7–20.5 years) using the UCLA Activity Score, modified Harris hip score (mHHS), WOMAC, and radiographic analysis. The mean age at PAO was 26 years (range, 10-60 years) and consisted of 113 female patients (132 hips [86%]) and 16 male patients (22 hips [14%]). Complications were graded using the validated Clavien-Dindo system. Complications were assessed for each hip and the highest complication grade was assigned to the hip if multiple complications occurred. We divided complication grades into three groups for analysis: no complications, Grade 1 complications, and complications that deviated from the standard postoperative course (Grades 2, 3, and 4). There were no Grade 5 complications. Variables with significant (p < 0.05) univariable associations with complications were considered for inclusion in a multivariable model. Outcome variables (mHHS and WOMAC) at the most recent followup visit were analyzed using a generalized estimating equation approach. Analysis of variance was used to compare UCLA at the most recent followup among the complication classes. Results: Major complications defined as Clavien-Dindo Grade 3/4 occurred in 14 hips (9%). After controlling for potential confounding variables, we found that increasing body mass index (BMI) (odds ratio [OR], 1.16; 95% confidence interval, 1.05-1.25; p = 0.004) was associated with increased risk of complication. In contrast, greater surgeon experience was associated with a decreased risk (OR, 0.3; p = 0.002). Complications were associated with postoperative pain and activity, WOMAC (mean ± SD: 0 complications = 1.5 ± 15.1, 1 complication = 4.3 ± 4.1, 2-3 complications = 3.8 ± 4.6; p = 0.020) and UCLA scores (mean ± SD: 0 complications = 7.8 ± 2, 1 complication = 6.7 ± 2.1, 2-3 complications = 6.5 ± 2; p = 0.003). Conclusions: Most hips undergoing PAO have few complications. The most common major surgical complication is nonunion. Increasing BMI was a predictor of having a complication, and surgeon experience decreased complication risk. Having a complication adversely affected long-term pain and activity. To minimize complications and maximize outcomes, a patient's BMI should be assessed preoperatively and those with excessive BMI should be counseled on the increased risk of complications. In an experienced surgeon's hands, PAO has few complications at mean 10-year followup and a low risk of permanent disability. Level of Evidence: Level III, therapeutic study.